Efficacy and safety of oral proprietary Chinese medicines in the treatment of stable chronic obstructive pulmonary disease: a network meta-analysis - Yan, Hao; Zhang, Jingwen; Yan, Hutao; Yang, Dandan (Frontiers in Pharmacology, 2026)
BackgroundA variety of oral proprietary Chinese medicines (OPCMs) have clinical efficacy in the adjunctive treatment of stable chronic obstructive pulmonary disease (COPD). However, the OPCM with the best therapeutic effect is not yet clear. Thus, a network meta-analysis (NMA) is leveraged to evaluate the best efficacious OPCM for the adjunctive treatment of stable COPD.MethodsRandomized controlled trials (RCTs) related to the adjunctive treatment of stable COPD with OPCMs were searched in PubMed, Web of Science, Embase, Cochrane Library, China National Knowledge Infrastructure, Wanfang, and VIP. The search period was up to 1 April 2024. Study screening and data extraction were performed according to predefined inclusion and exclusion criteria. The assessment of bias in the included studies was carried out using the Cochrane risk of bias tool version 2 (RoB 2.0). Statistical analyses were performed utilizing Stata version 17.0 (64-bit) and R software (version 4.3.3).ResultsThe database retrieval yielded 7,572 articles in total. Ultimately, 64 articles were included in the analysis. Compared to routine treatment (RT), the Yi-qi-gu-biao pill_RT improved the forced expiratory volume one-forced vital capacity (FEV1/FVC) ratio (mean difference [MD] = 15.343, 95% credible interval [CrI]: 10.233, 20.182). Jin-shui-bao capsule_RT improved tumor necrosis factor-alpha (TNF-α) levels (standard mean difference [SMD] = 2.92, 95% CrI: 2.07, 3.77). Shen-ling-bai-zhu powder_RT improved partial oxygen pressure (MD = 17.17, 95% CrI = 7.43, 26.93). The Yi-fei capsule_RT improved FVC (MD = 0.609, 95% CrI = 0.249, 0.696) and FEV1 (MD = 0.621, 95% CrI = 0.217, 1.023). However, no statistically significant differences were observed between the interventions for the modified Medical Research Council (mMRC) score, peak expiratory flow (PEF), partial pressure of carbon dioxide (PaCO2), total effective rate, or reduction in adverse reactions. Based on SUCRA, the Yi-qi-gu-biao pill_RT ranked highest for FEV1/FVC (SUCRA = 95.6%) and the mMRC score (SUCRA = 78.6%). The Jin-shui-bao capsule_RT showed advantages in TNF-α levels (SUCRA = 97.4%) and PEF (SUCRA = 69.9%). Shen-ling-bai-zhu powder_RT demonstrated the greatest improvement in PaO2 (SUCRA: 99.6%) and PaCO2 (SUCRA: 87.1%). Yi-fei capsule_RT was the most effective in improving FVC (SUCRA = 93.2%) and FEV1 (SUCRA = 80%). Bu-zhong-yi-qi granule_RT showed the highest SUCRA for improving the total effective rate (82.4%), and bai-ling capsules_RT exhibited the lowest incidence of adverse reactions (72.7%).ConclusionBased on the current findings, no specific OPCM has demonstrated noticeable effects across multiple aspects. However, it is evident that OPCM holds considerable potential as an adjunctive treatment for patients with stable COPD. Future high-quality and well-designed RCTs are necessary to further validate our findings.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024511142.